Regional Policy Coherence for the Great Green Wall Initiative: Restoring Land and Sustaining Peace: The Great Green Wall and the Climate– Peace–Security Nexus in Africa - African Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Climate change poses an escalating threat to Africa’s development, peace, and security. Despite contributing minimally to global emissions, the continent faces disproportionate loss and damage due to limited adaptive capacity and rising climate-related security risks including competition over natural resources, food and water insecurity, forced migration, and conflict. These converging challenges are increasingly shaping African policy agendas, with the African Union Peace and Security Council (AUPSC) recognising climate change as a key driver of instability and developing a Common African Position on Climate, Peace and Security (CAP-CPS). The African Union’s Great Green Wall Initiative (GGWI) offers a vital entry point to address this nexus by restoring degraded landscapes, strengthening community resilience, and advancing peace-positive development. Related initiatives such as the United Nations Decade on Ecosystem Restoration (2021–2030), the United Nations Convention to Combat Desertification (UNCCD) Peace Forest Initiative (2019), and the African Union Biodiversity Strategy and Action Plan (ABSAP) (2023 – 2030) provide complementary platforms to mainstream conflict-sensitive land restoration. Drawing on findings from the Africa Climate Security Risk Assessment (ACRA) and the African Union’s Climate Change, Peace and Security Nexus Report, this brief outlines how the GGWI can support integrated climate-security responses through three peace-positive pathways: (i) restoring natural buffers to reduce conflict, (ii) rebuilding social cohesion through participatory restoration, and (iii) supporting livelihood resilience to reduce instability and displacement. Key recommendations include integrating climate-security assessments into GGWI planning, aligning with the CAP-CPS and supporting African Union-led coordination, providing targeted readiness support for vulnerable and conflict-affected areas, promoting peace-positive nature-based solutions and carbon restoration pathways, operationalising early warning and peacebuilding tools, strengthening transboundary cooperation and mediation, expanding monitoring systems to track peace co-benefits, leveraging GGWI programmes as entry points for peace mediation and dialogue, and facilitating inclusive land governance and tenure security.